TOURIST PERCEPTION OF TANJUNG DURIAT ECOTOURISM JATIGEDE RESERVOIR AREA SUMEDANG REGENCY - Algiffary, Naufal; Djuwendah, Endah (Journal of Business on Hospitality and Tourism, 2019)
Jatigede Reservoir has eight attractive tourism potential to be visited by tourists who want to vacation in Sumedang Regency. One of the tourist attractions in the Jatigede Reservoir area that is often visited by tourists is Tanjung Duriat. In 2018 tourists visiting Tanjung Duriat experienced a drastic decline. The purpose of this study was to determine the perceptions of tourists visiting the Tanjung Duriat Tourism Center to be a material consideration to improve the quality of tourism facilities and increase the number of tourists coming. The design used is quantitative. The results of the study showed that most tourists from Tanjung Duriat Tourism came from outside the Sumedang Regency, male sex between the ages of 20-29 years with education. The graduate worked as an employee and had income above Rp. 3,000,000.00. Most of the visitors who come to Tanjung Duriat Tourism Center for vacation because this place is interesting to visit and the ticket price for admission is moderate, which means it is not expensive or not cheap. Most visitors budget for recreation costs to come to Tanjung Duriat Tourism Center below than Rp. 200,000.00. Almost all visitors who come with family use their transportation. Most visitors come to Tanjung Duriat Tourism Center for the first time and are interested in visiting again. The visitor's perception of the Tanjung Duriat Tourism Wana object can be concluded well. Although the tourists were unhappy with the road conditions that were considered harmful, the perceptions of the tourists towards the entire Wana Wisata object were considered good so that they could cover up the shortcomings.